Pharmacological Modulation of Behaviour, Serotonin and Dopamine Levels in Daphnia magna Exposed to the Monoamine Oxidase Inhibitor Deprenyl - Marina Bellot; Melissa Faria; Cristian Gómez-Canela; Demetrio Raldúa; Carlos Barata (Toxics, 2021)
This study assessed the effects of the monoamine oxidase (MAO) inhibitor deprenyl in Daphnia magna locomotor activity. The mechanisms of action of deprenyl were also determined by studying the relationship between behaviour, MAO activity and neurotransmitter levels. Modulation of the D. magna monoamine system was accomplished by 24 h exposure to two model psychotropic pharmaceuticals with antagonistic and agonistic serotonin signalling properties: 10 mg/L of 4-chloro-DL-phenylalanine (PCPA) and 1 mg/L of deprenyl, respectively. Contrasting behavioural outcomes were observed for deprenyl and PCPA reflected in decreased basal locomotor activity and enhanced habituation for the former compound and delayed habituation for the latter one. Deprenyl exposure inhibited monoamine oxidase (MAO) activity and increased the concentrations of serotonin, dopamine and the dopamine metabolite 3-methoxytyramine in whole D. magna extracts. Our findings indicate that D. magna is a sensitive and useful nonvertebrate model for assessing the effects of short-term exposure to chemicals that alter monoamine signalling changes.